Taḥqiqul Manāth in Madzhab-Contextualization of Non-Muslim Status in Indonesia - Muhammad Faeshol; Akhmad Khisni (Universitas Islam Sultan Agung, 2021)
The fatwa or decision of Bahtsul Masail which gave the status of non-Muslim Indonesians given the status of ḥarbi fī dzimmati tta'mīn was corrected by the Nahdlatul Ulama National Conference in Banjar City, West Java in 2019. Using a legal contextuality within the framework of the Imam Syafi'i school of thought, Nahdlatul Ulama 'stated Indonesian non-Muslims as non-Muslims are ordinary citizens who are the same as Muslim citizens and are not included in one of the four categories of kafirs in the schools with all the legal consequences. Contextualization as an effort to understand a law according to its context is carried out so that the law of fiqh madzhab in its application adapts to the changing and different context of reality. Ignorance of changes and differences in context will result in the application of the law of fiqh madzhab which violates the school itself.maḥall al-ḥukmi and ahl al-ḥukmi. The results of the National Conference as a correction to the different previous fatwas were carried out as a necessity so that the application of the law of fiqh madzhab was correct in its application. Not to change the law of the school of fiqh. The four categories of kafir remain in the madzhab as a kulli concept. But implementing it must be appropriatemaḥall al-ḥukmi her.And non-Muslims in Indonesia are not maḥall al-ḥukmi is right for the concept.